Improving students' mathematical communication skills through the guided inquiry learning model with Desmos - Salsabila; Sri Hastuti Noer; Agung Putra Wijaya (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
One of the essential skills students must develop in mathematics learning is mathematical communication. However, field observations indicate that students still exhibit weaknesses in this area. Therefore, it is necessary to implement a learning model supported by digital media that facilitates students in expressing and communicating mathematical ideas more effectively. The guided inquiry learning model, when integrated with interactive media such as Desmos, offers a promising alternative. Desmos is a dynamic graphing application that allows students to explore mathematical concepts visually and interactively, thereby supporting deeper conceptual understanding and communication. This study employed a quasi-experimental design aimed at examining the improvement of students' mathematical communication skills through the implementation of a guided inquiry learning model with Desmos. The population consisted of all ninth-grade students at SMP Negeri 45 Bandar Lampung in the 2024/2025 academic year, totaling 107 students across four classes. The samples were selected using a cluster random sampling technique and comprised class 9.3 (27 students) as the experimental group and class 9.2 (26 students) as the control group. The research design used was a posttest-only control group design. Quantitative data were collected through a mathematical communication skills test. Based on hypothesis testing using an independent sample t-test at a significance level of α = 0.05, the results showed that t-count > t-table (2.08 > 1.67). Thus, it can be concluded that the application of the guided inquiry learning model with Desmos significantly improves students' mathematical communication skills.